1996
DOI: 10.1152/ajpregu.1996.271.5.r1130
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic capillary pressure is estimated using triple vascular occlusion method in isolated canine liver

Abstract: We determined whether the triple vascular occlusion pressure (Pto), the equilibration pressure obtained when the hepatic artery, portal, and hepatic veins were occluded simultaneously, represented the capillary pressure (Pc) in isolated bivascularly blood-perfused canine livers. Effects of a bolus injection of histamine (0.1-60 micrograms), norepinephrine (NE; 1-600 micrograms), or acetylcholine (ACh; 0.01-10 micrograms) into the portal vein or the hepatic artery were also studied on vascular resistance distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
31
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…In the liver, little is known about the effect of changes in blood Hct on the longitudinal distribution of vascular resistance. Thus we examined the effect of different Hct on the longitudinal vascular resistance distribution in the rat liver.Norepinephrine constricts predominantly the presinusoidal vessels over the postsinusoidal vessels of hepatic veins (3,15,22,24). Maass-Moreno and Rothe (15), by using the doublelumen catheter inserted through the caval wall into hepatic vein in anesthetized dogs, reported that an infusion of norepinephrine caused a large increase in portal venous pressure but little change in pressure gradient from the large hepatic vein to vena cava.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the liver, little is known about the effect of changes in blood Hct on the longitudinal distribution of vascular resistance. Thus we examined the effect of different Hct on the longitudinal vascular resistance distribution in the rat liver.Norepinephrine constricts predominantly the presinusoidal vessels over the postsinusoidal vessels of hepatic veins (3,15,22,24). Maass-Moreno and Rothe (15), by using the doublelumen catheter inserted through the caval wall into hepatic vein in anesthetized dogs, reported that an infusion of norepinephrine caused a large increase in portal venous pressure but little change in pressure gradient from the large hepatic vein to vena cava.…”
mentioning
confidence: 99%
“…The responsiveness of the hepatic longitudinal vascular segments differs depending on vasoactive agents (3,23,24). The differences in the response of these vascular segments to a variety of stimuli are, in part, due to the intrinsic vasomotor properties of the blood vessels as well as their passive viscoelastic properties.…”
mentioning
confidence: 99%
“…In rat livers, histamine did not contract or dilate hepatic vessels [11]. On the other hand, norepinephrine predominantly contracts the presinusoidal veins over the postsinusoidal veins in dogs, rabbits, rats, and guinea pigs [4,7,9,11]. However, the effects of these vasoconstrictors have not been determined on hepatic vascular resistance distribution in mice.…”
mentioning
confidence: 90%
“…predominantly contracts the postsinusoidal veins with resultant hepatic congestion in dogs [9,10] and guinea pigs [11], but this substance constricts presinusoidal vessels in rabbits [4]. In rat livers, histamine did not contract or dilate hepatic vessels [11].…”
mentioning
confidence: 93%
See 1 more Smart Citation